Flor Yeast: New Perspectives Beyond Wine Aging - Legras, Jean-Luc; Moreno-Garcia, Jaime; Zara, Severino; Zara, Giacomo; Garcia-Martinez, Teresa; Mauricio, Juan C.; Mannazzu, Ilaria; Coi, Anna L.; Bou Zeidan, Marc; Dequin, Sylvie; Moreno, Juan; Budroni, Marilena (Frontiers in Microbiology, 2016)
The most important dogma in white-wine production is the preservation of the wine aroma and the limitation of the oxidative action of oxygen. In contrast, the ageing of Sherry and Sherry-like wines is an aerobic process that depends on the oxidative activity of flor strains of Saccharomyces cerevisiae. Under depletion of nitrogen and fermentable carbon sources, these yeast produce aggregates of floating cells and form an air-liquid biofilm on the wine surface, which is also known as the velum or flor. This behaviour is due to genetic and metabolic peculiarities that differentiate flor yeast from other wine yeast. This review will focus first on the most updated data obtained through the analysis of flor yeast with -omic tools. Comparative genomics, proteomics and metabolomics of flor and wine yeast strains are shedding new light on several features of these special yeast, and in particular, they have revealed the extent of proteome remodelling imposed by the biofilm life-style. Finally, new insights in terms of promotion and inhibition of biofilm formation through small molecules, amino acids and di/tri-peptides, and novel possibilities for the exploitation of biofilm immobilisation within a fungal hyphae framework, will be discussed.